(untitled) (Encuentros, 2022)
The present study sought to explore the relationships between auditory sensitivity, speech discrimination and a set of linguistic performance variables in a sample of older adults, through a quantitative, non-experimental, correlational study with multivariate analysis, in a sample of sixty-one (61) older adults, selected according to inclusion and exclusion criteria. Tonal audiometry, logoaudiometry, and the Battery for the Assessment of Aphasic Disorders (BETA) were used as instruments. Results indicated age-related hearing loss (ARHL) with a decline in high frequencies, preserved speech discrimination, and the relationship between hearing sensitivity and speech discrimination in linguistic performance in specific domains such as naming, verbal fluency and hearing compression.